Przezwiska antroponimiczne i przydomki w Pisarzowej - Małgorzata Kowalska (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2010)
The article concerns anthroponymic cognomina and nicknames in Pisarzowa. In the field research, the total number of 142 cognomina and nicknames were collected. In the small community of the village, cognomina and nicknames lightly dominate the surnames. Several motivational types of cognomina and nicknames may be distinguished in the collected material. They stem both from proper nouns (most often from personal names and surnames, geographical and place names), and from all kinds of common nouns. Those originating from appellatives are more numerous than those based on proper nouns. In Pisarzowa, unofficial anthroponymic descriptions function in the singular as individual names, e.g. Piwniczka, and in the plural as family names, e.g. Abycioki. The shift from surnames to cognomina is a process that may not always be observable. There are many ways of forming cognomina, such as onymisation, i.e. using appellatives, or trans-onymisation, i.e. using proper nouns. In small communities cognomina and nicknames are an important identifying element. In Pisarzowa the phenomenon is productive: practically every inhabitant of the village is nicknamed.